Melacak Perkembangan Filsafat Ilmu: Tinjauan Historis dan Logika Penalaranya - Asy'ari, Ary; Sibawaihi, Sibawaihi; Usman, Usman; Ridwan, Mahfudz (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2024)
The relationship between science and humans is close. Philosophically, there are differences in education between Islamic and Western education. Islamic education sees students as creatures of Allah and society who have potential in accordance with their nature, while Western education sees students as free individuals with their potential. The aim of this research is to determine the history of the development of the philosophy of science in Islam and its reasoning. This research uses a qualitative research approach with a historical approach. Data was collected through literature research and other data sources from books and other relevant documents. The research results are presented in the form of a story that is easy to understand using narrative analysis techniques. Attempts to translate Greek books into Arabic began the development of Islamic philosophy of science. Furthermore, Islam has a special epistemology for acquiring knowledge, which consists of three modes of thinking: Bayani, Burhani, and Irfani. Bayani's way of thinking is textual, while Irfani's is Sufi.